Gender Representation in English Textbook Used in Grade x of Senior High School - Abidah, Sa’wanatul; Sutama, Putu (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2019)
This study aims at finding how English textbook published by the Ministry of Education and Culture of Indonesia for Grade X of senior high school represents gender. It is a descriptive work using content analysis as its design in looking at how gender is represented in the book both quantitatively and qualitatively.The findings showed that the text book is generally gender friendly in which it represents women and men in mostly equal manner. However, it is still not free from stereotyping attached to its female and male characters. Furthermore, the differences in verbosity, the use of question form and intensifiers by female and male characters are identified.   Key words : gender representation, English textbook, Grade X